Dynamics in benthic community composition and influencing factors in an upwelling-exposed coral reef on the Pacific coast of Costa Rica - Stuhldreier, Ines (2015)
https://peerj.com/articles/1434/#supp-1 https://peerj.com/articles/1434/#supplemental-information